The Effect of Subjective Well-Being, Peer Support, and Self-Efficacy on Student Engagement of Class X Students of Four State Senior High School in Sidoarjo [Pengaruh SWB, PS, dan Efikasi Diri terhadap SE Siswa Kelas X di Empat SMAN di Kabupaten Sidoarjo] - Tania Nurmalita; Nono Hery Yoenanto; Duta Nurdibyanandaru (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2021)
An initial survey showed that school students at the Sekolah Menengah Atas Negeri (SMAN; State Senior High School) level in the Sidoarjo Regency of East Java Province, Indonesia, suffered low levels of student engagement (SE). This research examined the impact of subjective well-being, peer support, and self-efficacy on the student engagement of the students in the Class 10 of four SMAN in the Sidoarjo Regency. 328 students were involved in this research, filling in a survey related to the four variables of the study. The results of regression testing indicated that subjective well-being, peer support, and self-efficacy had significant influence on increases in student engagement (SE). The implication of this research was that the efforts by the school, parents, and other parties was related to attention being given, outside of improvement in the quality of the academic atmosphere. Psychological well-being, peer support, as well as increases in self-efficacy, may assist students to become actively involved in the learning process. Survey awal menunjukkan siswa di tingkat Sekolah Menengah Atas (SMA) Kabupaten Sidoarjo memiliki student engagement (SE) yang rendah. Penelitian ini mengkaji dampak dari subjective well-being, peer support, dan efikasi diri terhadap student engagement (SE) pada siswa kelas X yang berasal dari empat Sekolah Menengah Atas Negeri (SMAN) di Kabupaten Sidoarjo. 328 siswa terlibat dalam penelitian ini dengan mengisi survei terkait empat variabel studi. Hasil uji regresi menunjukkan bahwa subjective well-being, peer support, dan efikasi diri memberikan pengaruh signifikan terhadap peningkatan student engagement (SE). Implikasi penelitian ini adalah adanya upaya sekolah, orangtua, dan pihak lain terkait untuk memberikan perhatian di luar peningkatan kualitas atmosfir akademik. Kesejahteraan psikologik, dukungan sosial teman sebaya, maupun peningkatan efikasi diri dapat membantu siswa lebih terlibat aktif dalam proses pembelajaran.